Multiple Choledochal Cysts: A Case Report - Rezki, Wenny Rahmalia; Yusri Dianne Jurnalis; Budi Pratama Arnofyan (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Choledochal cysts (CC) are congenital dilatations of the biliary tree, characterized by varying degrees of cystic dilatation at various segments of the biliary tract (extrahepatic or intrahepatic), may be detected at any age and in any portion of the bile duct. This study was aimed to present the management of multiple choledochal cyst case. Case presentation: A 9 year old boy was brought by his mother to the emergency department at Dr. M. Djamil General Hospital Padang with chief complaint abdominal pain that’s getting worse 2 weeks before admission. Abdominal pain first complained by the patient since age of 4, the pain was felt all over stomach area, not localized, not radiated, not corelated with meal time, colicky, relieved with paracetamol. USG results: Choledochal cyst, Helicobacter pylori infection, elevated liver enzymes due to suspect suppression of choledochal cyst. Abdominal CT-Scan with contrast results: Intrahepatic and extrahepatic choledochal cyst (type IV A). Conclusion: Patients was diagnosed with multiple choledochal cysts, diffuse peritonitis, Helicobacter pylori infection, and familial short stature.